Finite element simulation of drying of mango - S. Janjai (2018)
A two-dimensional finite element model was developed to simulate moisture diffusion in mango fruit during drying. The diffusivity and shrinkage of mango used in this simulation were determined experimentally. Moisture diffusivity of mango fruit was determined by minimising the sum of squares of the residuals between experimentally determined and numerically predicted data. Shrinkage of the mango flesh during drying was determined experimentally and an equation based on a physical concept was fitted to the experimental data. A computer program in Compaq Visual FORTRAN version 6.5 was developed to simulate the finite element model and it satisfactorily predicted the moisture diffusion during drying. Moisture content profiles of the mango fruit were also predicted and the profiles gave accurate pictures of the movement of moisture inside mango fruit during drying. This model can be used to provide information on the dynamics of moisture movement without the need for measurements and can also be used to provide design data of dryers. © 2008 IAgrE.